1995
DOI: 10.1364/ao.34.002476
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer gratings for solar energy applications

Abstract: Diffractive optical structures for increasing the efficiency of crystalline silicon solar cells are discussed. As a consequence of the indirect band gap, light absorption becomes very ineffective near the band edge. This can be remedied by use of optimized diffraction gratings that lead to light trapping. We present blazed gratings that increase the optically effective cell thickness by approximately a factor of 5. In addition we present a wideband antireflection structure for glass that consists of a diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
213
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(218 citation statements)
references
References 11 publications
5
213
0
Order By: Relevance
“…This argument is similar in nature to the one of Ref. 9. The results we see here also match well with what has been suggested recently by Refs.…”
Section: A Interpretation Of Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This argument is similar in nature to the one of Ref. 9. The results we see here also match well with what has been suggested recently by Refs.…”
Section: A Interpretation Of Resultssupporting
confidence: 93%
“…Such structures have been thoroughly analyzed in the past, [8][9][10] but have attracted renewed attention lately. [11][12][13][14] Recently, it has been shown that periodic structures may increase light trapping beyond that of the Lambertian 4n 2 limit, 15,16 but with a significant angular dependency.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the only way to assess absorption enhancement is by rigorous numerical solution of Maxwell's equations for the multilayer structure, taking into account the exact nature of all interfaces. Based on such techniques, significant absorption enhancement has been predicted for binary and ideally blazed gratings; [29][30][31] tailoring of surface textures for solar cells is still a rather young field. 32 Moreover, not all theoretically imaginable shapes are also feasible for solar cell processing.…”
Section: Resonance Excitation In Periodic Devicesmentioning
confidence: 99%
“…For the case of mono-crystalline silicon, periodic photonic nanostructures have been barely investigated optically but they have not been integrated in a solar cell so far [17][18][19][20][21][22].…”
mentioning
confidence: 99%